2015
DOI: 10.1016/j.imbio.2014.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory cells induced by acute toxoplasmosis prevent the development of allergic lung inflammation

Abstract: The increased prevalence of allergies in developed countries has been attributed to a reduction of some infections. Supporting epidemiological studies, we previously showed that both acute and chronic Toxoplasma gondii infection can diminish allergic airway inflammation in BALB/c mice. The mechanisms involved when sensitization occurs during acute phase would be related to the strong Th1 response induced by the parasite. Here, we further investigated the mechanisms involved in T. gondii allergy protection in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…gondii infection suppressed Th2-related inflammation in a mouse model of birch-pollen-induced allergic airway inflammation [ 16 ]. These results were confirmed by Fenoy et al [ 17 , 18 ] further describing a major role for regulatory T cells in thoracic lymph nodes of T . gondii -infected mice in preventing allergic lung inflammation in their model.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…gondii infection suppressed Th2-related inflammation in a mouse model of birch-pollen-induced allergic airway inflammation [ 16 ]. These results were confirmed by Fenoy et al [ 17 , 18 ] further describing a major role for regulatory T cells in thoracic lymph nodes of T . gondii -infected mice in preventing allergic lung inflammation in their model.…”
Section: Introductionsupporting
confidence: 79%
“…The expansion of regulatory T cells in thoracic lymph nodes after infection with T . gondii was recently described, also showing that adoptive transfer of these cells resulted in suppression of allergic airway inflammation [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that IL-10 is not a key cytokine involved in TLA-induced allergy prevention and this is in agreement with findings by Fenoy et al ., who could show that T . gondii -induced suppression of allergy is IL-10-independent 47 . We have previously shown that decreased levels of antigen-specific IL-10 in cell cultures could be explained by increased uptake via upregulated IL-10 receptor 48 .…”
Section: Discussionmentioning
confidence: 96%
“…gondii infection strongly diminish the development of an allergic airway inflammation [ 33 ]. The mechanisms behind this phenomenon included the deviation to a Th1 phenotype plus the induction of regulatory cells [ 37 , 38 ] that might result from the activity of many different immunomodulatory proteins.…”
Section: Discussionmentioning
confidence: 99%